Deciphering MECP2-associated disorders: disrupted circuits and the hope for repair. (February 2018) - Qiu, Zilong
Highlights: MeCP2 is a regulator for transcription, microRNA processing and mRNA splicing. Multiple circuits contribute to defects of MECP2 -associated disorders. Manipulations of MeCP2 in adulthood can rescue behavioral deficiency. Non-human primate models may serve as platforms for translational studies. Abstract : MECP2 is a critical gene for neural development, mutations or duplication of which led to severe neurodevelopmental disorders, such as Rett syndrome (RTT) and autism spectrum disorders (ASD). Extensive works during the past decade yield ample insights into the molecular and cellular functions of MeCP2 in neural development. Furthermore, genetic manipulations in Mecp2 mouse models strongly suggested that deficiency in synaptic plasticity and various behaviors of Mecp2 null or transgenic mice could be rescued in adulthood. Further studies elucidating neural circuits responsible for symptoms in MECP2 -associated disorders in rodent and non-human primate models will shed light on the development of potential therapeutic interventions.